Water policy, management, and institutions: The role of pro-poor water allocation in the Yellow river basin - Wang, Jinxia; Zhang, Lijuan (International Food Policy Research Institute, 2010)
The Yellow River Basin (YRB) is the breadbasket of China. Rural areas constitute a major center of grain and cotton production, and, as a result, rural wealth is highly dependent on access to irrigation water. A changing climate and increasing competition from the urban and industrial sectors as well as the implementation of province-level water withdrawal quotas equivalent to 37 km3 since 1999 described below threaten the agricultural sector's sustained access to water resources.